Measuring destination competitiveness: an importance-performance analysis (IPA) of six top island destinations in South East Asia. Issue 3 (3rd March 2020) - Mustafa, Hasrina; Omar, Bahiyah; Mukhiar, Sharifah Nadiah Syed
ABSTRACT: The aim of this study is to measure competitiveness of six island destinations in South East Asia. Face-to-face survey interviews with 1644 international tourists from six top island destinations (Langkawi-Malaysia, Bali-Indonesia, Koh Samui-Thailand, Phuket-Thailand, Palawan-Philippines and Boracay-Philippines) were conducted. Seven dimensions namely safety & security, basic infrastructure, tourism infrastructure, nature, man-made attractions, people and hospitality; and culture and traditions were used to measure the relative competitiveness of each destination. The IPA grids indicated different competitive positions of each island, with each island exhibiting unique characteristics and strengths. Implications for both practitioners and policy makers are discussed.